Addressing the nonexercise part of the activity continuum: A more realistic and achievable approach to activity programming for adults with mobility disability? - Manns, P.; Dunstan, D.; Owen, N.; Healy, Genevieve (2012)
Participation in physical activity is fundamental for the maintenance of metabolic health and the prevention of major chronic diseases, particularly type 2 diabetes and cardiovascular disease. A whole-of-day approach to physical activity promotion is increasingly advocated and includes not only increasing moderate-intensity physical activity but also reducing sedentary time and increasing light-intensity activity (the "nonexercise" part of the activity continuum). This whole-of-day approach to tackling the challenge of inactivity may be particularly relevant for adults with mobility disabilities, who are among the most inactive segment of the population. Focusing on nonexercise activity by striving to reduce sedentary time and increase light-intensity activity may be a more successful place to begin to change behavior in someone with mobility disability. This article discusses what is known about the metabolic health consequences of sedentary behavior and light-intensity activity in adults with and without mobility disability. The concept of inactivity physiology is presented, along with possible applications or evidence from studies with adults with mobility disability. Mobility disability discussions and examples focus on stroke and spinal cord injury. Finally, clinical implications and future research directions related to sedentary behavior in adults with mobility disability are discussed.